2022
DOI: 10.3389/fimmu.2022.854202
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleosomes Accelerate Microglial Inflammation via C-Type Lectin Receptor 2D and Toll-Like Receptor 9 in mPFC of Mice With Chronic Stress

Abstract: Damage-associated molecular patterns (DAMPs) are the primary promoter of progressive neuroinflammation and are associated with chronic stress-related emotional disorders. The present study investigated the role and mechanism of extracellular nucleosomes and histones, the newly defined DAMPs, in mice with chronic stress. C57BL/6 mice were exposed to chronic unpredictable mild stress (CUMS) and corticosterone drinking, respectively, for 4 weeks. Negative emotional behaviors were comprehensively investigated. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Chronic stress can trigger not only previously well-recognized DAMPs but also extracellular nucleosomes and histones. Increased histones and nucleosomes were found in the cerebrospinal fluid of the CUMS mice, which positively correlated with IL-1β levels in PFC [44]. Higher levels of nucleosomes promoted microglial inflammatory signaling in a C-type lectin receptor 2D (Clec2d)-dependent manner, increasing oxidative stress and IL-1β secretion [44].…”
Section: Role Of Damage-associated Molecular Patterns (Damps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic stress can trigger not only previously well-recognized DAMPs but also extracellular nucleosomes and histones. Increased histones and nucleosomes were found in the cerebrospinal fluid of the CUMS mice, which positively correlated with IL-1β levels in PFC [44]. Higher levels of nucleosomes promoted microglial inflammatory signaling in a C-type lectin receptor 2D (Clec2d)-dependent manner, increasing oxidative stress and IL-1β secretion [44].…”
Section: Role Of Damage-associated Molecular Patterns (Damps)mentioning
confidence: 99%
“…Increased histones and nucleosomes were found in the cerebrospinal fluid of the CUMS mice, which positively correlated with IL-1β levels in PFC [44]. Higher levels of nucleosomes promoted microglial inflammatory signaling in a C-type lectin receptor 2D (Clec2d)-dependent manner, increasing oxidative stress and IL-1β secretion [44]. Knockdown of Clec2d in PFC reduced microglial inflammatory activation and depressive-like behavior in CUMS mice.…”
Section: Role Of Damage-associated Molecular Patterns (Damps)mentioning
confidence: 99%
“…A few KD studies have revealed the similar involvement of additional TLRs in chronic stress resilience; KD of cyclic adenosine monophosphate response element-binding protein (CREB) in the HPC of UCMS mice increased resilience to stress and was associated with the downregulation of TLR1 and TLR6 [10]. Increased TLR9, and increased Clec2d, a receptor involved in sensing cellular stress, were observed in the medial prefrontal cortex (mPFC) of UCMS mice, while the KD of the latter inhibited microglial inflammation and reduced stress-induced negative emotional behaviors [88]. This indicates that other TLRs should be investigated in chronic stress and that the TLR-NF-κB pathway is one of the main mechanisms contributing to inflammation and chronic stress.…”
Section: Tlrsmentioning
confidence: 99%
“…Lai et al expanded the role of CLEC2D serving as a sensor for cell death to detect histones released from necrotic cells 21 . CLEC2D has been found to carry histone-bound DNA complexes into endosomes, stimulating TLR9-mediated pro-inflammatory responses in macrophages and microglia 21 , 22 . Our recent findings demonstrate that CLEC2D recognizes glucuronoxylomannan from Cryptococcus neoformans to promote the p38-mediated production of arginase-1, leading to the induction of immunosuppressive activity of neutrophilic myeloid-derived suppressor cells (MDSCs), and subsequently inhibiting T cell-mediated anti-fungal responses 23 .…”
Section: Introductionmentioning
confidence: 99%